Caracterização do processo de desfolhação e da dinâmica de perfilhamento em azevém sob diferentes ofertas de forragem - Graminho, Larissa Arnhold (2014)
This study was conducted with the aim of generating information about the tillering process and contribute to the understanding of the defoliation process of Italian ryegrass (Lolium multiflorum Lam) utilized by lambs submitted to different herbage allowances: 6, 8 and 12 kg body weight DM/100 kg. The grazing method was intermittent. Pasture was utilized during 12 days and an accumulated thermal sum of 250 degree-days was the criterion to determine the grazing interval. The experimental design was completely randomized with repeated measures on time, three treatments and two area replication. It was used 35 marked tillers per paddock to determine the intensity and interval of defoliation. Tillering dynamics on the identification and counting of remaining living tiller and new appearance tillers. The intensity of defoliation is greater in 6 and 9% herbage allowances. The interval of defoliation is higher in forage herbage allowance 12%, intermediate in 9% and lower in the 6% offer. The rate appearance, survival and death of tillers, stability index of tillers number are similar for herbage allowances and differ according phenological stages of ryegrass. Different herbage allowances and phenological stages promote variable intensity and interval of defoliation. The advance of phenological stage increases tiller mortality and reduce the interval between defoliation.